Entre o casulo e a borboleta: olhares acerca da transfobia nas relações afetivas - Gregori, Juciane de (2019)
This study aims to question the requirement of linearity without loopholes between the construction of plural performativity and heteronormativity, its overall goal being to analyse the social dynamics of transphobia as violence perpetrated in the context of romantic and family relationships. Seeking fluidity between theoretical, methodological, technical and ethical aspects, this research is qualitative-based, is founded predominantly in queer theoretical references, and expands the discussion based on the literature of Judith Butler; it uses interdisciplinary material, which produces readings consistent with these theories from nonconformist realities specific to Brazil. Having as a field to develop data collection the State Centre of Reference for the rights of lesbians, gays, bisexuals and transgender people (LGBT) and the confrontation of homophobia of Paraíba (LGBT Space), dialogue circles were carried out, focusing on the participating research. It is considered that the dynamics of affectivity of cisnormative logics meet with transphobic violence and perpetuate a diversity of performativities and relational ties. Thus, transphobia, as a superimposed system on multiple violence, is realised by a spectrum of forms, with multi-faceted amplitudes and intensities. In the face of such situations, trans people become stronger and reinvent themselves, fostering claims with a set of interventions and confrontation. Highlighting the character of trans protagonism, which counteracts imposed subalternalism, this research seeks to contribute in the opening of possibilities that trace paths committed to an academic doing and a sociological knowledge focused on the (in)visible, for what does not want to be said, but echoes all the time in relationships: trans lives exist - (resist)!